Disrupting the status quo: fostering a practice of inclusion in engineering through post-secondary allyship training - Jocelyn Peltier-Huntley; Rosa Moazed (FACETS)
The traditionally male-dominated engineering profession requires greater inclusion and proportional representation of diverse groups to effectively solve complex global challenges. To foster inclusive practices, individuals involved in engineering education, including students, staff, and faculty, can be engaged, trained, and empowered to serve as “active allies”. In this study, researchers designed and trialed a blended training program meant to support potential allies to adopt a practice of inclusion. The 26 participants in our study included undergraduate and graduate students, staff, and faculty from a Canadian engineering college. Our study incorporated a transformative mixed methods design meant to qualify and quantify the impacts of the allyship course. Our findings show learners’ motivation and allyship competencies progressed because of the psychologically safe learning environment and course content. Additionally, participants experienced the largest improvements in understanding equity, diversity, and inclusion (EDI) language, which resulted in more frequent EDI conversations. However, conducting EDI training without an EDI organizational commitment poses a risk to sustained allyship behaviors. Our findings show that with organizational support, allyship training will promote inclusive behaviors necessary to create innovative, equitable, and diverse organizations—a necessary foundation for solving complex global problems.